Saluran Distribusi Hasil Tangakapan Ikan Kuniran (Upeneus sulphureus) di Pangkalan Pendaratan Ikan Desa Banyusangka Kecamatan Tanjung Bumi Kabupaten Bangkalan Madura - Muhammad Harris Akhyar; Didik Trisbiantoro (Universitas Mataram, 2024)
This research was conducted at Banyusangka Village TPI with the object of research on fish distribution, namely from fishermen, collecting traders, retailers. Data analysis in this research are: non-fixed cost, production cost, marketing margin analysis, profit percentage, marketing cost share, profit share, marketing margin distribution. The results showed that the age level of fishermen was 36-45 years old with a percentage of 45%. The average length of experience of fishermen is 9 to 13 years as a fisherman. The average profit per year is IDR 89,288,571 and profit per month is IDR 3,922,591, large traders are IDR 94,171,667 and profit per month is IDR 7,847,639. Small traders IDR.27,314,267 and profit per month IDR. 2.276.189. Analysis of the marketing margin of Rp.2000, the profit received by fishermen is 1.2%, the marketing cost is IDR.326,883 per month, the distribution of the marketing margin of fish traders is IDR.23,027.